Factors affecting successful treatment outcomes in pulmonary tuberculosis: a single-center experience in Turkey, 2005–2011 - Sengul, Aysun; Akturk, Ulku Aka; Aydemir, Yusuf; Kaya, Nurullah; Kocak, Nagihan Durmus; Tasolar, Fatma Turan (The Journal of Infection in Developing Countries, 2015)
Introduction: We aimed to describe the treatment outcomes in patients with bacteriologically confirmed pulmonary tuberculosis (PTB) and identify factors associated with successful treatment outcome. Methodology: The medical charts of patients with smear and/or culture-positive PTB who were treated between 2005 and 2011 at the Kocaeli Tuberculosis Dispensary, Turkey, were reviewed. Patients were categorized as having a successful (cured or with a completed treatment) or poor (treatment default, treatment failure, death) treatment outcome. The association of demographic and clinical factors, including gender, age, education, occupation, insurance, family size, living area, smear and culture positivity, retreatment, comorbidity, drug resistance, and cavity on radiography, with the success of treatment, was evaluated by univariate and multivariate analyses. Results: Of 738 patients (258 females, 480 males) with bacteriologically confirmed PTB, 683 (92.6%) had successful treatment outcomes. Of those with a poor outcome, 29 (3.9%) had treatment default, 18 (2.4%) died, and 8 (1.1%) had treatment failure. Young age, no previous treatment, no comorbidity, no drug resistance, and high education level were factors significantly associated with successful PTB treatment outcome (p < 0.05 for all). Conclusions: Treatment outcome was successful in young and educated PTB patients who had drug resistance, previous treatment history, and no comorbidities. Knowledge of the factors affecting treatment success will lead to the undertaking of specific measures in the management of PTB, which may help to decrease treatment failure.